Phylogenetic analysis of wheat cultivars in Kazakhstan based on the wheat 90 K single nucleotide polymorphism array. Issue 1 (30th July 2015) - Turuspekov, Yerlan; Plieske, Joerg; Ganal, Martin; Akhunov, Eduard; Abugalieva, Saule
Abstract : The recent introduction of Illumina single nucleotide polymorphism (SNP) arrays is an important step towards comprehensive genome-wide studies of genetic diversity in wheat. In this study, 90 cultivars of hexaploid spring wheat growing in Kazakhstan were genotyped using the high-density wheat 90 K Illumina SNP array. The analysis allowed the identification of 30, 288 polymorphic SNPs. A subset of 3541 high-quality SNPs were used for a comparison of 690 wheat accessions representing landraces and varieties, including those from Asia, Australia, Canada, Europe, Kazakhstan, USA and other parts of the world. Phylogenetic analysis showed a clear separation of wheat cultivars according to their geographic origin. In the phylogenetic tree, accessions from Kazakhstan and the USA formed two neighbouring clusters with a common node, and they were distinct from accessions from other regions of the world, including Europe. The results provide important new insights into the genetic relationships between diverse wheat accessions.